2009
DOI: 10.4271/2009-01-2673
|View full text |Cite
|
Sign up to set email alerts
|

Speciated Engine-Out Organic Gas Emissions from a PFI-SI Engine Operating on Ethanol/Gasoline Mixtures

Abstract: Engine-out HC emissions from a PFI spark ignition engine were measured using a gas chromatograph and a flame ionization detector (FID). Two port fuel injectors were used respectively for ethanol and gasoline so that the delivered fuel was comprised of 0, 25, 50, 75 and 100% (by volume) of ethanol. Tests were run at 1.5, 3.8 and 7.5 bar NIMEP and two speeds (1500 and 2500 rpm).The main species identified with pure gasoline were partial reaction products (e.g. methane and ethyne) and aromatics, whereas with etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 12 publications
2
27
0
1
Order By: Relevance
“…Therefore, it can be concluded that benzene emissions tend to increase under low temperature and to be reduced under oxygen-rich conditions. more likely caused by the reduction of aromatics in the fuel blends rather than changes in the fuel chemistry [59]. This trend of toluene emission is consistent with that of alcohol-gasoline blends [57].…”
Section: Benzene Toluene Ethylbenzene and Xylene (Btex) Emissionssupporting
confidence: 73%
“…Therefore, it can be concluded that benzene emissions tend to increase under low temperature and to be reduced under oxygen-rich conditions. more likely caused by the reduction of aromatics in the fuel blends rather than changes in the fuel chemistry [59]. This trend of toluene emission is consistent with that of alcohol-gasoline blends [57].…”
Section: Benzene Toluene Ethylbenzene and Xylene (Btex) Emissionssupporting
confidence: 73%
“…The Tier-2 emissions regulations provide a regulatory standard of 0.018 g/mile for formaldehyde but do not provide a standard for acetaldehyde, though this compound is included in EPA's list of mobile-source air toxic compounds that are produced by mobile sources [6]. These findings in general agree with a recent speciation study conducted at the Massachusetts Institute of Technology (MIT), with the exception that the MIT study did not report formaldehyde emissions [7]. This omission may be due to the use of a gas chromatograph equipped with a flame ionization detector to accomplish the speciation, as formaldehyde has a zero response in FID-based instruments.…”
Section: Ohc Speciation Resultssupporting
confidence: 58%
“…There are ongoing investigations of ethanol's effects on fuel systems, evaporative emissions, and gaseous emissions (Durbin et al 2007; Kar and Cheng 2009;Knoll et al 2009;Coordinating Research Council 2011), but few gasoline engine studies have examined its impact on PM emissions. The paucity of data is presumably because stoichiometric combustion in spark ignition engines naturally produces very low PM emissions, a few milligrams per mile (Maricq et al 1999), and because GDI is a new technology.…”
Section: Introductionmentioning
confidence: 99%